A rapid and sensitive LC–MS/MS method for analysis of iguratimod in human plasma: Application to a pharmacokinetic study in Chinese healthy volunteers. (17th July 2018) - Xia, Ying; Zhao, Shunbo; Gong, Meng; Ding, Li
Abstract: A rapid, sensitive and reproducible LC–MS/MS method was developed and validated to determine iguratimod in human plasma. Sample preparation was achieved by protein precipitation with acetonitrile. Chromatographic separation was operated on an Ultimate® XB‐C18 column (2.1 × 50 mm, 3.5 μm, Welch) with a flow rate of 0.400 mL/min, using a gradient elution with acetonitrile and water which contained 2 mm ammonium acetate and 0.1% formic acid as the mobile phase. The detection was performed on a Triple Quad™ 5500 mass spectrometer coupled with an electrospray ionization interface under positive‐ion multiple reaction monitoring mode with the transition ion pairs of m / z 375.2 → 347.1 for iguratimod and m / z 244.3 → 185.0 for agomelatine (the internal standard), respectively. The method was linear over the range of 5.00–1500 ng/mL with correlation coefficients ≥0.9978. The accuracy and precision of intra‐ and inter‐day, dilution accuracy, recovery and stability of the method were all within the acceptable limits and no matrix effect or carryover was observed. As a result, the main pharmacokinetic parameters of iguratimod were as follows: C max, 1074 ± 373 ng/mL; AUC0–72, 13591 ± 4557 ng h/mL; AUC0–∞, 13, 712 ± 4613 ng h/mL; T max, 3.29 ± 1.23 h; and t 1/2, 8.89 ± 1.23 h.